Effects of Tamarind (Tamarindus indicus Linn) seed extract on Russell's viper (Daboia russelli siamensis) venom - Khin, Maung Maung; Zaw, Lynn Aung (Malaysian Society of Parasitology and Tropical Medicine, 2012)
Snake bite has been regarded as an important health problem in Myanmar since early 1960's. In the recent years, there has been growing interest in alternative therapies and therapeutic use of natural products, especially those derive from plants. In Myanmar and Indian traditional medicine, various plants have used as a remedy for treating snake bite. The present study was carried out to evaluate the effects of alcohol extract of Tamarind (Tamarindus indica Linn.) seed on some biologic properties of Russell's viper (Daboia russelli siamensis) venom (RVV). The Phospholipase A2 (PLA2) enzyme, coagulase enzyme and caseinolytic enzyme activities of Russell's viper venom (RVV) were reduced when mixed and incubated with the extract. When the RVV and the different amount of extracts were preincubated and injected intramuscularly into mice, all of them survived, but all the mice in the control group died. On the other hand, when RVV were injected first followed by the extract into mice, all of them died. If the extract was injected near the site where Russell's viper venom was injected, all the mice survived for more than 24 hours and the survival time prolonged but they all died within 96 hours. In conclusion, according to the results obtained, the extract neutralizes some biologic properties of the Russell's viper venom and prolonged the survival time if the extract was injected near the site where the Russell's viper venom was injected.